2011
DOI: 10.1017/s0007114511000523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breed effects onn-3 PUFA metabolism with dietary flaxseed oil supplementation in dogs

Abstract: PUFA are important for human and animal health. To our knowledge, previous studies investigating the metabolism of PUFA in dogs have not examined breed differences. The aim of the present study was to evaluate the potential to elongate PUFA in two pure breeds of dogs. Plasma fatty acid composition (%) was measured in dogs during 3 weeks supplementation with flaxseed oil (57 % a-linolenic acid (ALA) and 17 % linolenic acid (LA)) at the rate of 100 ml/kg food following 4 months of feeding an identical standard b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…This is consistent with the findings of our previous study, wherein breed differences in dogs were demonstrated for LCn-3FA metabolism when plasma n-3FA was analyzed (Purushothaman et al, 2011). However, in this study, the expression levels of the 3 genes were different in both breeds even prior to supplementation.…”
Section: Different Gene Expression Between Two Breedssupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with the findings of our previous study, wherein breed differences in dogs were demonstrated for LCn-3FA metabolism when plasma n-3FA was analyzed (Purushothaman et al, 2011). However, in this study, the expression levels of the 3 genes were different in both breeds even prior to supplementation.…”
Section: Different Gene Expression Between Two Breedssupporting
confidence: 92%
“…Diets were offered once daily (300 g for beagles and 600 g for greyhounds), and there were no refusals during the 3-week supplementation period. The detailed composition of the basal and supplementation diets has been described previously (Purushothaman et al, 2011).…”
Section: Animals and Dietmentioning
confidence: 99%
See 3 more Smart Citations